2020
DOI: 10.21203/rs.3.rs-16396/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude and determinants of newborn mortality in neonatal intensive care unit hospitals in Ethiopia: a systematic review and meta-analysis

Abstract: Background: In Ethiopia, the neonatal mortality rate has not shown significant changes over time and is among the highest in the world. Exploring the magnitude and the causes of neonatal mortality in the hospital where neonatal intensive care unit is functioning could be supremely important to step towards improving the quality of neonatal care services. Therefore, this review aimed to explore the pooled magnitude and determinates of neonatal mortality in the neonatal intensive care unit hospitals in Ethiopia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similar to our results, neonates born before 37 weeks of GA in Brazil were six times more likely to die compared with term neonates [21]. Our finding is also in agreement with other earlier studies [22,23], both of which showed 3-fold higher NM rate among preterm neonates compared with term neonates in 2020.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our results, neonates born before 37 weeks of GA in Brazil were six times more likely to die compared with term neonates [21]. Our finding is also in agreement with other earlier studies [22,23], both of which showed 3-fold higher NM rate among preterm neonates compared with term neonates in 2020.…”
Section: Discussionsupporting
confidence: 93%
“…Gestational age as well as the birth weight, has a significant relationship with infant mortality and its components including malnutrition in the first 28 d of life, susceptibility to infections, respiratory distress and traumas during childbirth, and development of chronic non-communicable diseases (NCDs). Previous studies also showed an association between gestational age and neonatal mortality ( 24 26 ). Preterm and low birth weight infants are more susceptible to complications such as hypothermia, infections, and birth asphyxia (resulting in tissue hypoxia and multiorgan failure) ( 25 ).…”
Section: Discussionmentioning
confidence: 74%
“…1 Such anomalies are the fifth leading cause of morbidity and mortality in children worldwide. [2][3][4][5] They affect 8.1 million newborns worldwide, and more than 3.3 million babies die annually from these problems. In addition, over 3.2 million children have disabilities owing to congenital anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to identify contextual factors to help prevent neonatal deaths and disabilities caused by congenital anomalies. [2][3][4][5] Few studies have been conducted on predictors of congenital anomalies in Ethiopia. 7,8,27 Therefore, the aim of the current study was to identify the predictors of congenital anomalies in the Harari region and the Dire Dawa administration in eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%